PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Wenny Claudia; Agustin Ekadjaja (Universitas Kristen Krida Wacana, 2013)
AbstractThe purpose of this research is to get the empirical proof whether or not variables of managerial ownership, institutional ownership, investment decisions, financing decisions, and profitability, either partially or simultaneously, have significant impacts on the value of manufacturing firm listed on the Indonesia Stock Exchange in period 2010-2012. This research was conducted by means of multiple regression linear analysis with the help of a computer programme of SPSS version 20.0. With a 95% confidence level, the result of this research conducted partially from 2010 to 2012 is that managerial ownership had significant impacts on firm value, institutional ownership had no significant impacts on the firm value, investment decisions had significant impacts on firm value, financing decisions had no significant impacts on firm value, and profitability had significant impacts on firm value. While conducted simulatenously, the result shows that variables of managerial ownership, institutional ownership, investment decisions, financing decisions, and profitability significantly impacted the firm value. It is reccommended that, for the next research, more independent variables and research samples be used and a longer period be needed as well.Keywords : Managerial Ownership, Institutional Ownership, Investment Decisions, Financing Decisions, Profitability, Firm Value